Ֆրանսիայի դերակատարումը Կիլիկիայի հիմնախնդրի «լուծման» գործում - Մարտիրոսեան, Արման (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Окончание Первой мировой войны положило начало сложному процессу передислокации и перекройки политической карты послевоенного мира. Интересы союзников Великобритании и Франции пересекались, особенно на Ближнем Востоке, где глубокие разногласия по поводу раздела бывшей Османской империи долгое время не позволяли сторонам прийти к общему согласию. Особый интерес в этот период представляет глубокий и всесторонний анализ специфики ближневосточной политики Франции, которому и адресована данная статья. В этом контексте представлены важные причины франко-турецких отношений, Киликии, политика уступок французских властей в «решении» проблемы и мотивы ее катастрофических последствий․ The end of World War I marked the beginning of a difficult process of rearranging powers and restructuring the postwar world political map. The interests of former allies England and France were intersected especially in the Near East, where deep contradiction around the division of territories of former Ottoman Empire did not allow them to come to terms for quite a long period. In this period, the in-depth and comprehensive analysis of the French Near Eastern policy, which is the goal of our study, is of special interest. The compliant policy of France towards the “solution” of Cilician problem, which could be explained by financial-economic interests, as well as the reasons and motives of its catastrophic outcome for Cilician Armenians are presented in this context.